Intelligence and security informatics : Pacific Asia Workshop, PAISI 2014, Tainan, Taiwan, May 13, 2014. Proceedings - Chen, Hsinchun; Wang, G. Alan; Wang, Jau-Hwang; Chau, Michael (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the Pacific Asia Workshop on Intelligence and Security Informatics, PAISI 2014, held in Tainan, Taiwan, in May 2014 in conjunction with PAKDD 2014, the 18th Pacific-Asia Conference on Knowledge Discovery and Data Mining. The 7 revised full papers presented together with one short paper were carefully reviewed and selected from 10 submissions. The papers are organized in topical sections on regional data sets and case studies, cybercrime, information security engineering and text mining.